Stability analysis and evaluation of surrounding rock of ultra-deep shaft under complicated geological conditions - Hou, Kuikui; Zhu, Mingde; Hao, Yingjie; Yin, Yantian; An, Long (Frontiers in Earth Science, 2023)
The construction of deep underground engineering is greatly influenced by complex geological conditions such as high stress, faults, and fracture zones, which significantly affects the stability of the project. Taking the construction of 1,915-m-deep shaft in Sanshandao Gold Mine as the engineering background, which passes through many different strata and multiple fracture zones, the stability evaluation and failure zone prediction during its excavation under the influence of high stress, uneven strata, and fault structure are studied. Results show that the range of the failure zone increases significantly when the shaft passes through the fracture zone or different lithologies, and the maximum depth is 5.28 m. When the distance between the rock mass in the borehole and the excavation face is greater than 48 m, the disturbance superposition effect basically disappears. This paper provides theoretical and data support for the design and construction of the kilometer-deep shaft in Sanshandao Gold Mine.